The End Is the Beginning: Parkinson’s Disease in the Light of Brain Imaging - Bellucci, Arianna; Antonini, Angelo; Pizzi, Marina; Spano, PierFranco (Frontiers in Aging Neuroscience, 2017)
Parkinson’s disease (PD), the most common neurodegenerative disorder is characterized by abnormal accumulation of α-synuclein aggregates known as Lewy bodies (LB) and loss of nigrostriatal dopaminergic neurons. Recent neuroimaging studies suggest that in the early phases of PD, synaptic and axonal damage anticipate the onset of a frank neuronal death. Paralleling, even post mortem studies on the brain of affected patients and on animal models support that synapses might represent the primary sites of functional and pathological changes. Indeed, α-synuclein microaggregation and spreading at terminals, by dysregulating the synaptic junction, would block neurotransmitter release, thus triggering a retrograde neurodegenerative process ending with neuronal cell loss by proceeding through the axons. Rather than neurodegeneration, loss of dopaminergic neuronal endings and axons could thus underlie the onset of connectome dysfunction and symptoms in PD and parkinsonisms. However, the manifold biases deriving from the interpretation of human brain imaging data hinder the validation of this hypothesis. Here, we present pivotal evidence supporting that novel comparative brain imaging studies, in patients and experimental models of PD in preliminary stages of disease, could be instrumental for proving whether synaptic endings are the sites where degeneration begins and initiating the factual achievement of disease modifying approaches. The need for such investigations is timely to define an early therapeutic window of intervention to attempt disease halting by terminal and/or axonal healing.